PENGARUH MODEL PEMBELAJARAN SCRAMBLE TERHADAP HASIL BELAJAR SISWA KELAS XI IPA SMA SWASTA FAJAR MAS LAHUSA PADA MATERI SISTEM PENCERNAAN MAKANAN PADA MANUSIA - Nafaeli Laia (TUNAS : Jurnal Pendidikan Biologi, 2023)
Education is an attempt to guide children with the aim of developing the potential of students so that they become human beings who believe and are devoted to God Almighty, have noble character, are healthy, knowledgeable, capable, creative, independent, and become democratic and responsible citizens. The aim of this research is to determine the effect of the Scramble Learning Model on the Human Digestive System. This type of research uses quasi-experimental research (quasi-experiment). Quasi-experimental research is research intended to determine whether there are consequences of something imposed on the subjects being studied. The population of this study was the entire class of Class XI Science which consisted of two classes, namely class XI-IPAa as the experimental class and class XI-IPAb as the control class. Based on the results of the research conducted, there is an influence of the Scramble Learning Model on the Food Digestive System Material in Humans for the 2022/2023 Academic Year because the Scramble learning model makes students more creative in learning and thinking, studying the material more relaxed and without pressure because the Scramble learning model allows students to learn while playing and the material provided is impressive and always remembered by students. This can be seen from the results of data analysis, the average learning outcomes of students in the control class in the initial test were 60.86 (adequate) and the final test was 68.52 (adequate), while the average learning outcomes in the experimental class in the initial test were 64.44 (adequate) and the final test. 81.66 (good). The results of the two-party hypothesis test (t test) of the final test data obtained tcount = 6.69 and ttable = 2.00488 at a significance level of 5%, because tcount > ttable then Ha is accepted and Ho is rejected, namely there is an influence of the Scramble Learning Model on the Food Digestive System Material in Human Learning Year 2022/2023.